Pediatric pulmonary infection caused by oral obligate anaerobes: Case Series - Zhijun, Lai; Wenhai, Yang; Peibin, Zeng; Qingming, Luo (Frontiers in Pediatrics, 2023)
Background: Pneumonia is quite common in people with chronic bedridden, severe malnutrition and underlying diseases of cerebral palsy. Although poor oral hygiene and inadequate airway protection are risk factors, case reports of childhood pneumonia caused by oral obligate anaerobes are rare.We reported 4 cases of oral anaerobic pneumonia and empyema diagnosed by the pediatric intensive care unit (PICU) of our hospital.Discussion: No bacteria were detected in sputum bacterial culture, pleural water bacterial culture and blood culture of the four children.Considering that multiple sputum cultures were negative, the pleural effusion and bronchoalveolar lavage fluid were subjected to next-generation sequencing (NGS) to identify the pathogen causing pneumonia. The results found oral obligate anaerobes represented by Parvimonas micra and Porphyromonas gingivalis. After identifying the pathogenic bacteria, we changed to piperacillin tazobactam combined with metronidazole for anti-infection treatment, and the pneumonia in the above patients was improved.In addition, all four patients had different basic medical histories, and long-term bed rest, severe malnutrition, poor oral hygiene and insufficient airway protection were all high risk factors for oral anaerobic pneumonia in these children.Oral obligate anaerobes are one of the pathogens to consider for pneumonia in the elderly, but they may be easily overlooked in pediatric groups.Therefore, when receiving children with high-risk factors, we should be alert to the possibility of oral obligate anaerobic bacteria infection. Educating family members to pay attention to children's oral hygiene plays an important role in preventing oral obligatory anaerobic bacteria pneumonia. NGS can be used as a rapid diagnostic method when sputum culture cannot distinguish between pathogens.